Addressing Challenges and Development in Enforcing International Laws on Child Soldiers: The Need for Legal Reform - Obinna Nnanna Okereke; Uche Nnawulezi; Salim Bashir Magashi; Septhian Eka Adiyatma; Kasim Balarabe (Journal of Law and Legal Reform, 2024)
The purpose of this paper is to examine the challenges of enforcing the international legal framework on child soldiering. The paper reveals that, as the offense of child soldiering escalates, the multi-dimensional scope for protecting child soldiers spans various legal regimes under international law. It argues that, despite several prohibitive norms established in International Humanitarian Law (IHL), International Human Rights Law (IHRL), the International Labour Organization (ILO), and International Criminal Law (ICL), their application or enforcement against child soldiering remains ineffective and inadequate due to numerous impediments and challenges. This is because "law on paper," like a baby in the womb, must align with "law in action" to achieve adequate effectiveness. The methodology employed is doctrinal research. Major gaps were identified, and the paper provides comprehensive recommendations to enhance the enforcement of global treaties against child soldiering. The paper concludes with recommendations to address the technical and legal complexities associated with child soldiering.